Analysing Literature-Based Innovation Output Indicators: The Italian Experience - Enrico Santarelli; Roberta Piergiovanni (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1994)
This paper presents the results of a study on the product innovations introduced in the Italian market in 1989 and reported in a selected number of trade journals. The analysis of data collected by means of this literaure-based counting procedure confirms that R&D oriented industries and large firms do not in Italy have a marked competitive advantage in innovation. The country appears to be instead characterized by a significant presence of consumer goods industries and small firms in innovation. Our data indicate a statistically significant association between trade competitiveness and strength in product innovation, and show the comparatively higher capacity for product innovation of some of the industries in which Italy achieves a positive performance in international trade. Moreover, the presence of spillovers as the regional level from both private and public R&D expenditures proves to be positively correlated with the development of product innovations. Finally, small firms with fewer than 50 emloyees appear to be more innovative than is usually believed to be the case.
Keywords: 330